American unemployment : past, present, and future - Stricker, Frank (University of Illinois Press, 2020)
"The history of unemployment and many concepts surrounding it remain a mystery to many Americans. Frank Stricker believes we need to understand this essential thread in our shared past. American Unemployment is an introduction for everyone that takes aim at misinformation, willful deceptions, and popular myths to set the record straight: -Workers do not normally choose to be unemployed. -Workers do not normally choose to be unemployed. -In our current system, persistent unemployment is not an aberration. It is much more common than full employment, and the outcome of elite policy choices. -Labor surpluses propped up by flawed unemployment numbers have helped to keep real wages stagnant for more than forty years. -Prior to the New Deal and the era of big government, laissez-faire policies repeatedly led to depressions with heavy, even catastrophic, job losses. -Undercounting the unemployed sabotages the creation of government job programs that can lead to more high-paying jobs and full employment. Written for non-economists, American Unemployment is a history and primer on vital economic topics that also provides a roadmap to better jobs and economic security"--